2021
DOI: 10.1007/s12274-021-3961-3
|View full text |Cite
|
Sign up to set email alerts
|

Graphene foam/hydrogel scaffolds for regeneration of peripheral nerve using ADSCs in a diabetic mouse model

Abstract: The functional recovery of peripheral nerve injury (PNI) is unsatisfactory, whereas diabetes mellitus (DM) and its related complications further attenuate the restoration of diabetic PNI (DPNI). Adipose-derived stem cells (ADSCs) are promising candidates for treatment of DPNI due to their abundant source, excellent differentiation and paracrine ability. Our results showed that ADSCs remarkably enhanced the proliferation and migration of Schwann cells and endothelial cells, and tube formation. Mechanistically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Meanwhile, Figure S5b, Supporting Information reveals that GSGC can improve the viability of Schwann cells when compared with pure hydrogel groups, which exhibits the good proliferation ability of graphene skeleton and is consistent with previous report. [49] Our results also demonstrate the excellent biocompatibility of DDSAT for further in vivo application and additional graphene can promote proliferation of Schwann cells.…”
Section: Cytotoxicity and Viability Assaysupporting
confidence: 59%
“…Meanwhile, Figure S5b, Supporting Information reveals that GSGC can improve the viability of Schwann cells when compared with pure hydrogel groups, which exhibits the good proliferation ability of graphene skeleton and is consistent with previous report. [49] Our results also demonstrate the excellent biocompatibility of DDSAT for further in vivo application and additional graphene can promote proliferation of Schwann cells.…”
Section: Cytotoxicity and Viability Assaysupporting
confidence: 59%
“…The in vitro results indicated that ADSCs can regulate Nrf2/HO-1, NF-κB, and PI3K/AKT/mTOR signaling pathways, showing multiple functions in reducing oxidative stress and inflammation and regulating cell metabolism, growth, survival, proliferation, angiogenesis, differentiation of Schwann cell, and myelin formation. Furthermore, the in vivo results demonstrated ADSCs-loaded composite scaffold significantly promoted nerve recovery and inhibited the atrophy of targeted muscles [ 80 ]. Likewise, some recent cases with GBMs and these techniques (aerogel and foam) for NTE have been listed in Table 1 , although they are limited at present when compared with other techniques.…”
Section: Tissue-engineered Scaffolds With Gbm and Neural Tissuesmentioning
confidence: 99%
“…Thus, these results demonstrated that graphene-based nanoscaffolds can cure long-term peripheral nerve defects by promoting axonal regeneration and nerve function recovery. Graphene foam/hydrogel scaffolds significantly promote the recovery of sciatic nerves in vivo with no obvious organ lesions or damage (Huang et al, 2022). Qian et al (2018a) demonstrated that the GO/PCL nerve guidance conduit also successfully repaired sciatic nerve defects in rats, effectively promoting its functional and morphological recovery, and showed no obvious toxicity for the long-term.…”
Section: Graphene In Nerve Repairmentioning
confidence: 98%